Tedo Sakhokia and Abkhazia - Nikoleishvili, Avtandil (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2022)
One of the primary focal points of Tedo Sakhokia’s (1868-1956) multifaceted scientific, creative, and socio-political endeavors was his proactive involvement in addressing the challenges associated with Abkhazia. He not only opposed the colonial policies enacted by the Russian government in Abkhazia through his written works but also took practical measures. This is exemplified by his pivotal role in establishing the „Georgian Party“ of Abkhazia between 1895 and 1904. This political party regarded the resolution of two key issues as essential prerequisites for fostering the national consciousness of Abkhazia’s inhabitants: the official recognition of Georgian language services in churches and the implementation of Georgian-language education in schools. Tedo Sakhokia’s insights about Abkhazia are of significance as they provide us with a comprehensive understanding of the ethnic makeup of the local population. Specifically, according to his information, Georgians constituted the largest segment of Abkhazia’s inhabitants by the end of the 19th century. However, due to Russia’s colonial policies in the region, the number of foreign settlers, primarily Russians, steadily increased. According to the writer, this ethnic division of Abkhazia’s population resulted in the greatest hardships for the Abkhazians, who represented the smallest portion of the populace. While Tedo Sakhokia’s association with Abkhazia extends beyond the matters discussed herein, the aforementioned details offer a substantial foundation for acknowledging the role he played in addressing the challenges of Abkhazia through his creative pursuits and active practical endeavors.